O ENSINO DA TRIGONOMETRIA NO CICLO TRIGONOMÉTRICO, POR MEIO DO SOFTWARE GEOGEBRA - Bittencourt, Adilson Ortiz (2012)
In this study, through the difficulties encountered by students in solving problems in trigonometry, our aim was to create activities with the help of the software GeoGebra for the teaching of trigonometry in high school. The literature review covered the use of computational tools in education, trigonometry teaching and the use of the software GeoGebra in mathematics teaching. Moreover, were presented the resources used to build the product of the dissertation and an analysis of textbooks that approach contents of Trigonometry. Initially the survey was developed with 29 students of 2nd year of high school, in a public school in the municipality of Santa Maria, for whom a test was administered. With the correction of the solutions and their classification, it was found that the percentage of total or partially correct responses did not reach 50%. Thus, from the observation of these difficulties, a set of activities was planned to help teachers develop these topics as well as a way to allow students to learn autonomously, through videos. The activities, developed with help of GeoGebra, CamStudio and Screencasting, are available in two books, "Student Paper" and "Teacher Manual", that can be used in class attendance, in school computer labs and in Distance Education, and will be available on the website of the Master Professional course in Physics and Mathematics Teaching, of UNIFRA.